(untitled) (Research, Society and Development, 2020)
The aim of this paper was to verify the repercussions of maternal experience on mother-child interaction by examining its implications for child development through IRDIs in a sample of mothers of babies born in a medium-sized city and the outskirts of central Rio. Grande do Sul (RS). The study sample consisted of mother - baby dyads (n = 165) in a teaching hospital. For data collection, an interview script was used to investigate socioeconomic, demographic, obstetric, psychosocial information and maternal experience. The Clinical Indicators of Risk for Child Development (IRDIs) were also used. When assessing the association between the absence / presence of risk for infants (IRDIs) and the absence / presence of maternal emotional alteration, a significant result was found. There is a higher proportion of babies at risk when the mother presents emotional alteration in the postpartum period.